KEWAJIBAN PENCANTUMAN INFORMASIHARGA PRODUK DI RESTORAN A&W BANDARA SULTAN SYARIF KASIM II KOTA PEKANBARUBERDASARKAN UNDANG-UNDANG NOMOR 8TAHUN 1999 TENTANGPERLINDUNGAN KONSUMEN - Haq, Miftahul; Magdalena Sihombing, Trina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
BasedonArticle 7 of Law Number 8 of 1999 concerning Consumer Protection, it is regulated that business actors are required to provide correct, clear, and honest information regarding goods and/or services. This study aims to explain the obligation to include product price information at the A&W Restaurant at Sultan Syarif Kasim II Airport, Pekanbaru City based on Law Number 8 of 1999 concerning Consumer Protection. The method used in this research is sociological law research. A&W Restaurant at Sultan Syarif Kasim II Airport Pekanbaru City carries out sales procedures in accordance with the A&W Restaurant franchise standard and is willing to compensate for all losses suffered by consumers if their employees are proven to have violated sales procedures. The obstacle in carrying out the obligation to include product price information at the A&W Restaurant at Sultan Syarif Kasim II Airport in Pekanbaru City is the ignorance of consumers. Consumers who feel aggrieved can sue A&W Restaurant at Sultan Syarif Kasim II Airport Pekanbaru City to the Pekanbaru City Consumer Dispute Resolution Agency (BPSK) or to the Pekanbaru District Court.Keywords: Consumer Protection, Business Actors, Obligations